L´imaginaire fantastique chez nodier et l´inspiration biblique - Boruszko, Graciela (2012)
Charles Nodier, pioneer writer of the fantastic narrative in France, transfers biblical images into his stories. The transposed image is studied in parallel with the original image. This analysis explores from a comparative approach the intersections of literary narrative, the transposition of biblical images and the results of the insertion of those modified images in a new network of meaning. The intertextuality generated from this exchange, favors the creation of a new cosmogony that without hesitation incorporates the biblical world, proposing a new interpretation of the supernatural cosmos.